IMMUNOSTIMULANT POTENTIAL OF OYSTER MUSHROOM NUGGET (Pleourotus ostreatus) - Ardhia Deasy Rosita Dewi; Yayon Pamula Mukti (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
Oyster mushrooms are widely known as having high beta glucan content. Beta glucan is a water insoluble fiber that indicates an immunomodulator with increasing the activity of NK cells in the bloodstream which provides immune effect. Oyster mushroom nuggets are processed oyster mushrooms that can be proven containing the highest beta glucans. This study aims to observe the immunostimulant potential of oyster mushroom nuggets in BALB/c mice by analyzing its white blood cell profile, spleen and liver histopathology. The research method is conducted through orbital sinus of the rat's eye using a microhematocrit to count total leukocytes, lymphocytes, and granulocytes with the Delayed Type Hypersensitivity test. The 18mg/kg body weight oyster mushroom nugget can increase lymphocytes cells 7.2 ± 1.22 103/µl. It is significantly different from control group. Immunostimulatory activity also was proven with the widening of the white pulp of the spleen with the growth of young lymphocytes after being given oyster mushroom nuggets of 18 mg/kg body weight.